ABUNDANCE AND DISTRIBUTION OF KERANG DARAH (Anadara granosa) IN INTERTIDAL ZONE MONOSPESIESMANGROVE ECOSYSTEM Avicennia alba IN THE ANAK SETATAH VILLAGE KEPULAUAN MERANTI REGENCY RIAU PROVINCE - Abdurrahman, M.; Tanjung, Afrizal; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in March 2017 in the village of Anak Setatah, The District of West Rangsang, The Kepulauan Meranti regency of The Riau Province, aims to determine the abundance and the distribution of kerang darah (Anadara granosa), ingredients organic sediments, and The relationships between sedimentary organic content and abundance of kerang darah (A.granosa). To achieve these objectives it has been done three activities, namely: a) The calculation of the abundance of kerang darah (A.granosa) and measurement of water quality in the intertidal zone of mangrove forests monospesies Avicennia alba. b) Analysis of the distribution of kerang darah (A.granosa) in each zone (c) Analysis of samples of organic material in Marine Chemistry Laboratory of Marine Science Department, and (d) Analysis of sedimentary organic content relationships and abundance of kerang darah (A.granosa). An abundance of kerang darah highest at the lower zone and the lowest at the upper zone. Kerang darah have a clustered distribution patterns. Relations sedimentary organic matter content and the abundance of kerang darah (A.granosa)is positive and very weak.Keywords: Kerang Darah (A.granosa),The Abundance, Distribution,Intertidal, Mangrove and Relationships